GAMBARAN KARAKTERISTIK KUNJUNGAN PASIEN DENGAN KELUHAN SESAK NAPAS DI IGD RUMAH SAKIT SWASTA DI TEMANGGUNG JAWA TENGAH - Persi Susana; Diah Pujiastuti; Dwi N.Heri S; Nimsi Melati (STIKES Pemkab Purworejo, 2024)
Background: Shortness of breath is a condition where breathing is difficult and threatens death if immediate action is not taken. High air humidity, extreme weather changes and a large proportion of the population smoking can trigger shortness of breath. Objectives: This study aims to describe the characteristics of patient with shortness of breath complaint’s visit in the Emergency Room in Priavte Hospital in Temanggung, Central Java. Method: This research employed a quantitative descriptive method and purposive sampling research design. The total research sample was 40 respondents. The data was collected using a questionnaire, analyzed using univariate analysis, and processed using the frequency distribution formula. Results: The results of the research showed that the majority were 18-40 years old (42,5%), male (52.5%), primary school graduates (27.5%), farmers (37.5%), had internal disease (90 %), active smokers (52,5%), had respiratory frequency more than 21 x/m (85%), precipitating factors due to comorbidities (27.5%), shortness of breath not due to injury (97.5%). Conclusion: The most common characteristics are productive age 18-40 years, male, primary school graduates, farmers, internal disease, respiratory frequency more than 21 x/m, precipitating factors due to comorbidities, and non-traumatic causative factors. Suggestion: Future researchers are expected to explore the relationship between factors that trigger shortness of breath in asthma patients.